Analisis Dampak Konten Karakter Anomali dalam Media Digital Terhadap Perkembangan Imajinasi dan Identitas Anak Usia Dini - Masruroh, Abrorinnisail (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This article aims to examine the impact of anomalous character content in digital media on early childhood development. The research was conducted using a qualitative approach through a literature review of relevant books and scientific journal articles. The analysis was based on Bandura's social learning theory, Piaget's cognitive development theory, and Erikson's psychosocial development theory. The results of the study showed that anomalous characters in digital media act as symbolic models that can influence children's behaviour through the process of observational learning. In the preoperational stage, these characters are easily assimilated into children's symbolic imagination, while in the early psychosocial development stage, they can contribute to the formation of children's identity, especially in the initiative versus guilt phase. These findings indicate that the impact of anomalous character content is complex and influenced by content quality, frequency of exposure, and the level of adult supervision. This study emphasises the importance of managing and supervising the use of digital media so that the content consumed by children can support the healthy and adaptive development of their imagination and identity.